Humanizing STEM-Based Learning (Science, Technology, Engineering, and Mathematics) for the Transformation of Islamic Education in the 21st Century - Saehu Abas; Dian Alirahman, Agus; Mabrur, Hajjin (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
The development and progress of time always requires changes and innovations, including in the field of education and Islamic Education learning approach. The purpose of this research is to discuss theoretical and practical findings about integrated learning, namely Science, Technology, Engineering, Mathematics (STEM) learning innovation in Islamic Education. The method used in this research is a type of qualitative research with a literature review approach, examining and analyzing various sources of literature related to the research topic to be studied. The results showed that Islamic education learning that is integrated with STEM-based learning can use a learning approach: (1) Problem Based Learning; (2) Project Based Learning; (3) Inquiry-Based Learning; (4) Game Based Learning; (5) Digital Based Learning; (6) Collaborative Learning; (7) Hands on Learning.